Development and assessment of a methodology for the implementation of strategic manufacturing initiatives - Minarro Viseras, Enrique (Cranfield University, 2004)
The competitiveness and growth in the manufacturing sector is critical for the UK economy. It is imperative that the design and improvement of manufacturing systems is a constant and dynamic task in the British manufacturing environment. Unfortunately, many companies are still facing major difficulties during the implementation of strategic decisions derived from the formulation of manufacturing strategies. Current project management methodologies and techniques provide inadequate support for managers facing the implementation of strategic manufacturing initiatives (SMI). Therefore, the intention of this research is to provide a rigorous and successful SMI implementation methodology whose structure and contents include the most critical aspects relevant to the strategic manufacturing environment. The research described in this thesis has set out to form a SMI implementation methodology through a structured research programme. Initially existing literature related to SMI implementation methods was reviewed and analysed. A pilot methodology was then formed by contrasting literature against a list of key success factors in the implementation of strategic manufacturing initiatives determined from a worldwide survey. The pilot methodology was evaluated by a selection of practitioners, and results were used to refine the methodology. Finally, a validation test in a manufacturing organisation was conducted through a case study demonstrating the feasibility, usability and usefulness of the methodology. The fully tested and refined methodology is presented as a workbook in the appendix of this thesis. The outcome of this research is a structured step by step methodology which is an aid to the implementation of strategic manufacturing initiatives. The work described in this thesis has made a significant contribution to the knowledge on how to go about the implementation of strategic manufacturing initiatives.